Bilan, perspectives et éléments de stratégie. Secteur des industries manufacturières - Jouandet-Bernadat, Roland (L'Actualité économique, 1974)
AbstractThe main features of the manufacturing industries in the Province of Quebec are well known. Those industries are heavily concentrated in the Montreal area. They sell an important part of their output outside the Province. They exhibit structural weaknesses. Their importance in the Canadian economy has been declining in the past 25 years.We should not be too optimistic about the situation since 1971. Some officials claimed that the Province has known a new start in the manufacturing sector but the statistical facts do not confirm such a view.The Province therefore needs a really new strategy. The article tries to outline some of the constraints and features of this new strategy.